USING COOP-COOP METHOD TO IMPROVE THE STUDENTS’ NATURAL SCIENCE LEARNING COMPETENCES - Lila Pangestu Hadiningrum (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2019)
Abstract:This study aimed at finding out: (1) the extent to which the implementation of e-media (powerpoint learning and macromedia flash) innovations using the coop-coop method improved IPA (natural science) learning competencies especially in mastering the concept of the fifth grade students especially class B; (2) The ways to overcome the obstacles faced in the application of powerpoints and macromedia flash using the coop-coop method. This research used the classroom action method with the steps planning, implementation, observation and reflection (parallel srtucture). Data analysis was an interactive analysis. From the whole cycle that had been done, it could be concluded that: (1) the use of powerpoint and macromedia flash using the coop-coop method improved the students in mastering the concepts of human and animal organs, and green plants materials; (2) constraints of the application of powerpoint and macromedia flash using coop-coop method could be overcome by determining and limiting the material and time.Abstrak:Penelitian ini bertujuan untuk mengetahui : (1) sejauh mana penerapan inovasi pembelajaran dengan media elektronik (powerpoint dan macromedia flash) menggunakan metode co-coop dapat meningkatkan kompetensi belajar IPA khususnya dalam penguasaan konsep kelas VB Sekolah Dasar (SD); dan (2) cara mengatasi kendala yang dihadapi dalam penerapan powerpoint dan macromedia flash dengan metode co-coop. Penelitian ini menggunakan metode tindakan kelas dengan langkah-langkah menyusun rencana, pelaksanaan atau tindakan, observasi dan refleksi. Analisa data adalah analisis interaktif. Dari keseluruhan siklus yang telah dilakukan dapat disimpulkan bahwa (1) penggunaan powerpoint dan macromedia flash dengan metode co-coop mampu meningkatkan kompetensi belajar IPA khususnya dalam penguasaan konsep anggota tubuh manusia dan hewan, serta bagian pada tumbuhan; dan (2) cara mengatasi kendala dalam penerapan powerpoint dan macromedia flash dengan metode coop-coop dengan pembatasan materi dan waktu.